Comparison of the Clinical Diagnosis and Subsequent Autopsy Findings in Medical Malpractice - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
The rate of diagnostic error has not declined over the last 30 years despite the improvement in diagnosis methods. Today, the probability to encounter a major diagnostic change in autopsy is still high. The special autopsy that provides clinicians the necessary feedback is performed seldom in our country. This study has been started upon the claim that the malpractice cases in scope of forensic cases could be a very useful database. About 525 cases with faulty medical application that resulted in death have been encountered according to the cases that have been sent to the Forensic Medical Institution, which has been the consultative authority of the Ministry of Justice between the years 2001 and 2005. Among these, 375 cases on which autopsies have been conducted are included in the scope of the study. The cases with and without major diagnostic changes have been compared in aspects of gender, age groups, and period spent in health units. When the concordance between autopsy and clinical diagnosis for the 375 cases that were included in the study is examined, it can be seen that clinical diagnosis is verified with autopsy in 49.1% of the cases whereas neither autopsy nor clinical diagnosis was encountered in 14.7% of them. The diseases where diagnostic faults are mostly encountered are ruptured aortic aneurysm, myocardial infarction and pneumonia. The majority of the cases without a clinical diagnosis comprises of complications that occur after operations. In the study, considerable major diagnostic changes were realized after autopsy, which shows that autopsy has an important place in Turkey in spite of the improved methods of diagnosis. Also, in the cases with major diagnostic changes, the medical malpractice rate was high. This shows that autopsy is influential in revealing medical malpractice failures. In the study, we found out that the number of autopsies was high in the cases with a malpractice claim. We aim to increase this number. We are sure that such increment would increase decision accuracy.
Keywords: autopsy; medical malpractice; major changes; PREMORTEM